Modeling Earth materials from crustal to lower mantle conditions: A transferable set of interaction potentials for the CMAS system - Jahn, S; Madden, P (2007)
A fully flexible ionic interaction model (Aspherical Ion Model, AIM) is presented and applied to various relevant minerals and melts of the Ca-Mg-Al-Si-O (CMAS) system. The model reproduces accurately lattice parameters and thermoelastic properties of minerals in a wide range of compositions. Furthermore, its transferability range extends from the pressure and temperature conditions of the Earth's crust to the lower mantle. Thus, the AIM extends greatly the applicability of classical models in nanoscale computer simulations of Earth materials. The increased transferability compared to other interatomic potentials and the much more efficient calculation of interaction energies compared to first principles electronic structure calculations will allow larger scale simulations. The potential applications of the AIM to new fields of atomistic modeling in Earth sciences is discussed. © 2007 Elsevier B.V. All rights reserved.